Explicando el éxito de la innovación desde la perspectiva del cliente: La interacción entre la novedad para el cliente y las ventajas de la innovación; Explaining innovation success from the customer's perspective: The interplay between newness to customer and innovation advantage - Antonio Carmona Lavado; Rocío Aguilar Caro (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
– The effects of newness to customer and innovation advantage on innovation success have been extensively researched from different perspectives, especially in a B2C context. However, the joint influence of these two determinants has hardly been studied. This paper uses the theoretical framework of customer perceived value to explain the main effects of newness to customer and innovation advantage, as well as their interaction, on the financial and non-financial dimensions of innovation success in a B2B context. Data were collected through a telephone survey of a sample of 170 Spanish companies with up to three informants. To validate the measurement model, a confirmatory factor analysis was carried out, and for hypothesis testing, a hierarchical multiple regression, with a subsequent estimation of moderation using STATA's margins command. The results confirmed the predictions of the theoretical framework of customer perceived value for the financial performance of innovation, but not for the non-financial performance.
Keywords: O33; M21; 330; Product/service innovation; newness to customer; innovation advantage; innovation success; performance; confirmatory factor analysis; multiple regression; margins; STATA